Preservice and Inservice Teachers' Noticing of Explicit Instruction for Self-Regulated Learning Strategies - Michalsky, Tova (Frontiers in Psychology, 2021)
Contemporary theories of learning and instruction as well as a large body of research have pinpointed the benefits of effective self-regulated learning (SRL) for students’ academic achievements. Yet, research findings indicate that teachers’ actual promotion of students’ SRL strategies and students’ actual use of such strategies are less common than expected. To extend investigation of how and when teachers’ expertise develops regarding SRL-instruction practices in authentic classrooms, the current study compared preservice versus inservice teachers’ “noticing” of explicit SRL-teaching behaviors in videotaped classroom vignettes. Preservice teachers in a university teacher training program (N = 296) and inservice elementary, junior-high, and high-school teachers (N = 305) were presented with six online video-cases accompanied by questions about the videotaped teachers’ instruction of SRL planning, monitoring, and evaluation strategies. Results suggested that, overall, both preservice and inservice teachers failed to notice expert teachers’ explicit SRL-teaching. Furthermore, their noticing ability failed to increase over the career-span, with growing teaching experience. Thus, targeted instruction is recommended during both preservice training and inservice development programs to promote all teachers’ application of evidence-based explicit SRL-teaching strategies.